2021
DOI: 10.1136/bmjgh-2021-007315
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambulance prehospital time and maternal and perinatal outcomes in Sierra Leone: a countrywide study

Abstract: IntroductionSierra Leone, one of the countries with the highest maternal and perinatal mortality in the world, launched its first National Emergency Medical Service (NEMS) in 2018. We carried out a countrywide assessment to analyse NEMS operational times for obstetric emergencies in respect the access to timely essential surgery within 2 hours. Moreover, we evaluated the relationship between operational times and maternal and perinatal mortality.MethodsWe collected prehospital data of 6387 obstetric emergencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Second, additional time points were not captured to examine where specifically the delays in travel time occurred. For example, capturing dispatch time, response time, travel time, and prehospital time could have been additional time related variables that could have enhanced the results 22 . Due to these limitations, the result of this study needs to be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Second, additional time points were not captured to examine where specifically the delays in travel time occurred. For example, capturing dispatch time, response time, travel time, and prehospital time could have been additional time related variables that could have enhanced the results 22 . Due to these limitations, the result of this study needs to be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…79 Studies have found that the use of specialized vehicles such as motorlances (motorcycles modified to be used as ambulances) and helicopter Emergency Medical Services (HEMS) can lead to shorter response times than traditional ambulances, 61,69,80 which was in turn associated with improved health outcomes and lower mortality. 59,81,82 Factors that affected response times included the distance from the hospital, location, type of emergency, and ambulance mechanism. Additionally, several studies found that response times in rural areas were generally longer than those in urban areas [83][84][85] (Table 3 38,39,59,61,63,69,74,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] ).…”
Section: Status Of Prehospital Emergency Care Servicesmentioning
confidence: 99%
“…In Sierra Leone, a countrywide study demonstrated that maternal risk of death increased concurrently with National Emergency Medical Service (NEMS) operational times. 37 This implies that, improved maternal outcomes are likely to be noted with reduced delays of reaching the hospital. 37,38 The emergency system should be effective, affordable and adequate.…”
Section: Interventions Targeting Second Delaysmentioning
confidence: 99%
“…37 This implies that, improved maternal outcomes are likely to be noted with reduced delays of reaching the hospital. 37,38 The emergency system should be effective, affordable and adequate. 39…”
Section: Interventions Targeting Second Delaysmentioning
confidence: 99%